De mitos y realidades. Respuesta a Luciano Martínez - Coraggio, José Luis (2009)
This article represents the author’s response to critical commentary made in this section in the last edition by Luciano Martinez. The author maintains that the social and solidarity economy is a sphere under construction, in which several strands can be found. All of these approaches aim to move towards a different type of economy. This character as a developing realm can prompt doubts; this, however, should not lead to a paralyzing fatalism which allows the constant updating of the free market as a hegemonic institution. Far from a utopia to be denounced from a “realistic” viewpoint of economy, its concerns the construction of an economy that com-bines socio-politically regulated market mechanisms as well as relations of reciprocity and redistribution. The text also explores some of the elements that make up the solidarity and social economy.